To plead our own cause : personal stories by today's slaves - Bales, Kevin; Trodd, Zoe (Cornell University Press, 2008)
Boys strapped to carpet looms in India, women trafficked into sex slavery across Europe, children born into bondage in Mauritania, and migrants imprisoned at gunpoint in the United States are just a few of the many forms slavery takes in the twenty-first century. There are twenty-seven million slaves alive today, more than at any point in history, and they are found on every continent in the world except Antarctica. To Plead Our Own Cause contains ninety-five narratives by slaves and former slaves from around the globe. Told in the words of slaves themselves, the narratives movingly and eloquently chronicle the horrors of contemporary slavery, the process of becoming free, and the challenges faced by former slaves as they build a life in freedom. An editors' introduction lays out the historical, economic, and political background to modern slavery, the literary tradition of the slave narrative, and a variety of ways we can all help end slavery today. Halting the contemporary slave trade is one of the great human rights issues of our time. But just as slavery is not over, neither is the will to achieve freedom, "plead" the cause of liberation, and advocate abolition. Putting the slave's voice back at the heart of the abolitionist movement, To Plead Our Own Cause gives occasion for both action and hope. -- Publisher's Description